Can IPR Affect MNE’s Entry Modes? The Chilean Case (2017)
This paper analyzes the effect of stronger Intellectual Property Rights (IPR) on the entry modes chosen by MNEs in the Chilean market. MNEs can choose between exporting, introducing Foreign Direct Investment (FDI) and licensing to a domestic firm in Chile. We use plant-level data for the 2001–2007 and exploite the exogenous reform of IPR in Chile in 2005 to examine the effect of the change in IPR on the overall foreign presence in Chile, controlling for the activities of industries where high levels of technology transfer and imitation are important factors. The main results show that stronger IPR change the mode of entry chosen by MNEs. In this case, FDI is replaced by licensing. This is explained by Chile’s high absorptive capacity during this period. Moreover, we test whether this effect differs across high-tech and low-tech industries and conclude that the displacement of FDI is less severe in high-tech industries.